(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Human health, which can be affected by access to safe drinking water, or lack of it, is an area of common interest to the sustainable development goals (SDG, 6 target 1) and One health Initiative. Hence, this study examined the disease risk associated with drinking water sources in some rural agrarian communities in Kwara State, North-central Nigeria. Water from commonly used drinking water sources in the selected communities were tested for physicochemical properties (pH, Turbidity and Total dissolved solids content), and bacteriological quality. The health risks of the water sources were assessed in terms of presence and count of E. coli. Groundwater sources (wells and boreholes) were the predominant sources of drinking water in the communities. Only three (motorized boreholes) among the twenty-five water sources examined were free of coliforms. E. coli was found in thirteen water sources (a pond and twelves wells); with E. coli counts ranging from 2- 15 cfu/mL. The study revealed the need for urgent interventions to ensure the communities have access to safe water. The rural communities still depend heavily on groundwater as sources of drinking water, most of where portend had high level of disease risk.